ANALISIS EKONOMI SISTEM PLTMH DAN POMPA AIR SUNGAI YEH HA DI KABUPATEN KARANGASEM - Leba, G. I. M.; Sukerayasa, I. W.; Ariastina, W. G.; Giriantari, I. A. D.; Kumara, I. N. S. (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i01.p28, 2024)
Yeh Ha River in Ababi Village, Karangasem Regency, is a bathing spot utilized by locals for various purposes, fed by the Yeh Ha spring. Among its uses is filling a water tank with a capacity of 58.74 m3 to distribute water to 10 households. Initially, a waterwheel powered a mechanical pump without electricity. However, due to damage, a less efficient hydraulic ram pump replaced the waterwheel. The research aims to design a Microhydro Power Plant (PLTMH) and a water pump system. With these systems, it's expected to enhance the efficiency of filling the water tank and ensure project sustainability through economic analysis. Measurements indicate that Yeh Ha spring has a flow rate of 0.201 m3/s with a head of 4.6 m. Based on this, a crossflow turbine equipped with a centrifugal pump and variable frequency drive is chosen to meet the water needs of 12,277 people or 2,455 families. The investment for the PLTMH and water pump system is Rp3,191,330,505 with a project's economic life of 30 years. Feasibility analysis shows that the design is viable, with a positive net present value of Rp1,534,531,357 and Rp930,180,420 at discount rates of 10% and 12%, respectively. However, the benefit-cost ratio (BCR) is less than 1, at 0.48 and 0.29. The internal rate of return (IRR) is 17.6% and 15.5%, with a break-even point of 2,699,253 m3 sold, requiring a payback period of 9 years at a 10% discount rate and 10 years and 4 months at a 12% discount rate.